2013
DOI: 10.1136/oemed-2013-101584
|View full text |Cite
|
Sign up to set email alerts
|

Association between high temperature and work-related injuries in Adelaide, South Australia, 2001–2010

Abstract: There is a significant association between injury claims and temperature in Adelaide, South Australia, for certain industries and groups. Relevant adaptation and prevention measures are required at both policy and practice levels to address occupational exposure to high temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
148
7
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(180 citation statements)
references
References 31 publications
20
148
7
2
Order By: Relevance
“…In occupational studies, higher risk of heat-related illnesses and workrelated injuries are often reported among young workers (Bonauto et al, 2007;Maeda et al, 2006;Xiang et al, 2014;CDC, 2010), which can be attributed to various factors such as the lack of experience, training and skills and their assignment to more strenuous tasks or to jobs with increased hazards (Xiang et al, 2014;CDC, 2010). Our findings are however based on very low compensation numbers obtained in the 15-24 age group (n ¼ 35), and this explains that not all regions contributed cases to calculate the age-specific IRRs (only 6 health regions).…”
Section: Vulnerable Subgroupsmentioning
confidence: 97%
“…In occupational studies, higher risk of heat-related illnesses and workrelated injuries are often reported among young workers (Bonauto et al, 2007;Maeda et al, 2006;Xiang et al, 2014;CDC, 2010), which can be attributed to various factors such as the lack of experience, training and skills and their assignment to more strenuous tasks or to jobs with increased hazards (Xiang et al, 2014;CDC, 2010). Our findings are however based on very low compensation numbers obtained in the 15-24 age group (n ¼ 35), and this explains that not all regions contributed cases to calculate the age-specific IRRs (only 6 health regions).…”
Section: Vulnerable Subgroupsmentioning
confidence: 97%
“…There are convincing evidence with regard to the impact of ambient temperature on the mental/behavioural abnormalities of humans and the resulted accidents or injuries (Lee et al, 2014;Nitschke et al, 2013;Parsons, 2014;Xiang et al, 2014). However, no study has evaluated the association between temperature and dog bites, which account for an unneglectable proportion of external accidents and injuries in the hospital emergency system in China, particularly in Beijing where approximate 120,000 cases of dog bites were recorded in 2014 (56 cases per 10,000 population) (Beijing Center for Disease Prevention and Control, 2015;Beijing Municipal Bureau of Statistics, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…고온 및 저온 영역에서는 14.2~37.7℃에서 1℃ 상승할수록 직업성 손상 발생이 0.2%씩 증가한 다고 보고하였으며, -0.8℃ 이하에서 1℃씩 감소할 때마다 실외 직업성 손상은 2.3% 증가한다고 보고 하였다 (Morabito et al, 2014;Xiang et al, 2014 (Mahbub et al, 2015). 남성 근로자 81,346명을 대상으로 한 소음 추적연 구에서 상승된 청력 역치를 가진 90 dB 초과하는 소 음에 노출되는 근로자들은 정상 청력의 90 dB 미만 의 소음수준에 노출되는 근로자들에 비해 사고 발생 위험이 40%나 더 높게 나타났다 (Girard et al, 2004).…”
unclassified